Utilization of rapeseed pellet from fatty acid methyl esters production as an energy source - Ciunel, Krzysztof (Environmental technology, 2014)
Rapeseed pellet - crushed seed residue from oil extraction is a by-product of fatty acid methyl esters production process. As other types of biomass, it can either be burned directly in furnaces or processed to increase its energetic value. Biomass is renewable, abundant and has domestic usage; the sources ofbiomass can help the world reduce its dependence on petroleum products, fossil coal and natural gas. Energetically effective utilization of rapeseed pellet could substantially improve the economic balance of an individual household in which biodiesel for fulfilling the producer's own energetic demand is obtained. In this article, the experimental results of combusting rapeseed pellet in a calorimeter, combustion in a boiler heater and the analysis of the emissions level of different pollutants in exhaust fumes during different stages of biomass boiler operation are presented. It has been proved that the pellet, a by-product of biodiesel production, is not only a valuable substitute of animal fodder, but also an excellent renewable and environmentally friendly energy source, viable for use in household tap water heating installations